DI-094 The use of long-acting injectable formulations in subjects with schizophrenia: paliperidone palmitate versus others atypical antipsychotic drugs. (24th February 2014) - Scolari, C; Braus, A; Perani, L; Dimatteo, M; Schillaci, P; Moro, A; Gilberti, L
Abstract : Background: Schizophrenia is a serious mental health condition that causes disordered ideas, beliefs and experiences. The primary treatment is medicines. Non-compliance is one of the major problems of drop out. An important advance in improving adherence has been the introduction of long-acting injectable (LAI) formulations of atypical antipsychotics such as risperidone LAI (RLAI), olanzapine pamoate (OPLAI) and paliperidone palmitate (PLAI). Purpose: To examine the use and safety of PLAI since it became available and it started being used in our hospital in July 2012. To compare treatment costs of PLAI and RLAI. Materials and methods: Retrospective study conducted from July 2012 to July 2013 in our hospital. Patients diagnosed with schizophrenia at least one year ago were enrolled in the study. All patients had received RLAI (25–3.5–50 mg twice weekly) or PLAI (150–100–75–50 mg once monthly) or OPLAI (210–300 mg twice weekly) at least once in this period. Concerning use, safety and costs we analysed: number of patients, dose, adherence, adverse events (AEs) and cost per mean dose. Results: 90 patients (62 men and 28 women) mean age 39.27 years were included. Most of the patients (n = 72) received RLAI (mean dose 35.24 mg), 3 patients received OPLAI (mean dose 240 mg) and 15 patients received PLAI (mean dose 103.88 mg). Of the 15 patients treated with PLAI, 7 had a previous history of RLAI treatment, 8 had used a different typical or atypical antipsychotic (oral/ injectable). The switch was due to different causes: 33.33% lack of efficacy, 40% noncompliance 53.30% AEs. The most frequent AEs were extrapyramidal symptoms (EPS) and sexual dysfunction. Average annual cost per patient: PLAI cost about 1700 € more than RLAI. Conclusions: PLAI treatment has been used in patients having safety problems with other antipsychotic drugs. Experience with PLAI in our hospital has resulted in increased costs, probably due to the limited number of patients we considered. No conflict of interest.